Team and Project Work in Engineering Practices - Buch, Anders; Andersen, Vibeke (Nordic Journal of Working Life Studies, 2015)
In this article, we investigate teamwork amongst professionals in engineering consultancy companies in order to discern how teamwork affects the collaboration and work practices of the professionals. The article investigates how professional engineering practices are enacted in two engineering consultancy companies in Denmark where teamwork has been or is an ideal for organizing work. Through a practice-based lens, the article sets out to investigate, firstly, how discourses about team and project work affect engineering work practices; secondly, how technologymediated management is reconciled in teamwork practices; and thirdly, how team and project work affect engineering professionalism and collaborative work practices. A practice theoretical framework informs the analysis. Teamwork is investigated as a phenomenon enacted through the sayings, doings and relatings of practitioners in landscapes of practices and the interconnectedness of the practices is traced through the setup of specific ecologies in the sites.